Characterization Studies of Dual-Input Single-Output Converters for PV Applications. Issue 2 (4th March 2022) - Gupta, Nikita; Garg, Rachana; Kumar, Parmod
Abstract : Integrating renewable energy source with storage devices and the grid depends heavily upon the power electronic converters. Multi-input converters play an essential role in nanogrid and microgrid. In this paper, two novel cost-effective configurations of dual input single output (DISO) converters are designed for the low voltage PV applications in a standalone microgrid with the objective to improve both reliability and efficiency. The performance characterization models of these converters viz . reliability and sensitivity models are developed to validate the robustness and effectiveness when there is a parametric variation or under the influence of various stresses. Markov reliability models are developed to estimate the mean time to system failure, using the Military Handbook for Reliability Prediction of Electronic Equipment (MIL-HDBK-217F).